If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y+5(y+5)=14
We move all terms to the left:
6y+5(y+5)-(14)=0
We multiply parentheses
6y+5y+25-14=0
We add all the numbers together, and all the variables
11y+11=0
We move all terms containing y to the left, all other terms to the right
11y=-11
y=-11/11
y=-1
| -31=5(v-5)-3v | | 0x+6=8x+1 | | -8=2(x-3) | | 6-4s=4s+12 | | 3=5(x+4) | | 23=6(w+6)+7w | | 12-1.9y=4.9 | | 24+8=12x+40 | | 2e+2e=20 | | 6x-(11-2x)=16 | | 25-5k=-5 | | 4x-10+2x=14 | | √5x^2+x+√5=0 | | 53-15(t+3)=t+6 | | 6(x-10(=-18 | | 2/3(x-5)+1/4(x-2)=9/2 | | 5y+6(y-8)=7 | | 3(5x–7)=-66 | | 5^n-6=7^2n+3 | | -45x-81x-8x=12x-162x | | 6x+8-3x=-28 | | 3x+-4=12x-31 | | 4(4+5)=x^2 | | (1/2)x=(1/14)x+(6/7) | | 6x-16=7x+7 | | 3(x-1)=4(3x-4) | | 2a×a=12a | | 44-2v=3v+4 | | (2x-3)²-(x+5)²=0 | | 4+t=-8 | | 7x+19=11x+5 | | 7x-26°=180° |